Comportamiento Productivo y Calidad de Nuevos Cultivares de té (Camelliasinensis (L) Kuntze) en dos Localidades del Nordeste Argentino (Journal on studies and research of academic knowledge, 2016)
In order to characterize yield and quality of new cultivars of tea, in the last stage of the clonal selection, tests were conducted in two different environments of Argentine's tea region. The cultivars were CH14 (control), SG161, SG443, SG1420, SG1891, SG2257, SG2358, SG3191, SG3791, SG 7291, LM8, LM11e, LM19, 55/L5 and L7/28, its implantation was carried out in 2004 in the towns of Cerro Azul and GobernadorVirasoro, the design was randomized blocks with three replications. The yield evaluation was carried out during the period 2006/7 to 2012/13, with mechanized harvesting and collection of 12 to 14 days intervals. The samples for the sensorial quality were prepared as tea black in miniature tea factoryand are evaluated under the standard IRAM26640/ISO3103. Results showed that cultivars SG161, SG443 and SG1420 in both locations were significantly higher than the control; while the cultivars SG2358, SG3191, SG3791 and SG7291 were significantly superior to control only in Cerro Azul, while cultivars SG18/91, SG2257, LM8, LM19, L5/55 and L7/28 were significantly lower than the control in both locations. The correlation was high significant yields of both locations. The quality sensory was acceptable, with levels medium and high for all the cultivars in evaluation.
Keywords: Camellia sinensis; cultivars; yield; sensory quality